Communication Strategy for Financing Staff for Troubled Customers During the Covid 19 Pandemic at the Bank: Strategi Komunikasi Staf Pembiayaan pada Nasabah Bermasalah Saat Pandemi Covid19 di Bank - Juniarizky, Satriya Adiluhung; Utomo, Djarot Meidi Budi (Indonesian Journal of Innovation Studies, 2023)
This study aims to analyze and explain the communication strategy of financing staff to problematic customers during the covid19 pandemic at Bank Jatim Syariah Branch Sidoarjo. This research method uses qualitative methods, data collection is carried out by means of observation and interviews with 4 financing staff and 1 KDP (Credit Settlement) staff. The informant technique used purposive sampling and snowball sampling. The results of this study indicate that the communication strategy carried out by financing staff when collecting payments is always contacting customers, communicating in a healthy manner by communicating well, politely and politely not speaking harshly, this is to find information about customers who have problems then staff financing provides solutions to solve problems for customers so that they do not experience traffic jams and customer installments can run smoothly even though the payments are not in accordance with the principal installments.